A rare earth lanthanum modified thin glaze for da ya zhai imperial famille rose gold drawing porcelain and a preparation method thereof

CN122958061APending Publication Date: 2026-10-23WIZHE CHANGCHENG NETWORK TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611335158.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

若低软化组分在体系中无序分散并过早形成连续液相,容易阻碍内部气体排出,引起针孔、微泡或局部流釉;若整体软化不足,又会造成釉面微观起伏增大,不利于后续粉彩线条保持和描金层稳定结合

Benefits of technology

本发明通过协同调控骨架型熔块与镧改性封孔型熔块的粒径、软化行为及空间分布,构建具有受控成釉过程的薄釉体系。细粒、低软化温度的镧改性封孔型熔块经表面调节后吸附分布于粗粒、高软化温度的骨架型熔块表面,使其在烧成过程中优先于骨架颗粒周围形成局部液相,在保留排气通道的同时促进微孔填充;随后骨架型熔块进一步软化并完成整体玻化,从而协调排气、封孔与致密化过程,降低针孔、破泡和局部流釉风险,并拓宽稳定烧成窗口。同时,镧组分仅通过镧改性封孔型熔块引入,可使其随细粒功能相集中作用于局部液相形成区域;表面锚定后不再共同球磨,则有利于保持该粗粒—细粒空间组织状态。由此可改善薄釉表面连续性和平整度,减少粉彩纹饰扩散并提高描金层结合稳定性,实现薄釉烧成、粉彩清晰度和描金附着性能的协同提升,避免各组分和工艺措施仅产生简单叠加效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958061A_ABST
    Figure CN122958061A_ABST
Patent Text Reader

Abstract

The application discloses a rare earth lanthanum modified thin glaze for Da Ya Zhai imperial famille rose gold drawing porcelain and a preparation method thereof, and belongs to the field of ceramic glazes. The method comprises the following steps: preparing a coarse-grained high-softening-temperature skeleton type frit; preparing a fine-grained low-softening-temperature lanthanum modified sealing type frit; performing surface adjustment on the skeleton type frit by using polyethylene imine, so that the lanthanum modified sealing type frit is adsorbed and distributed on the surface of the particles, and a surface anchoring composite frit unit is formed; and then, under the condition of not performing common ball milling, the slurry is adjusted, and the rare earth lanthanum modified thin glaze is obtained. The lanthanum component is introduced only through the lanthanum modified sealing type frit. By controlling the particle size, softening behavior and spatial distribution of the two types of frits, the exhaust, sealing and densification processes in the firing process can be coordinated, the thin glaze pinholes and local glaze flow can be reduced, the firing stability can be improved, and the clarity of the famille rose decoration and the bonding stability of the gold drawing layer can be maintained and improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic glaze technology, and in particular to a rare earth lanthanum modified thin glaze suitable for Dayazhai Palace Famille Rose Gold-Painted Porcelain and its preparation method. Background Technology

[0002] The Da Ya Zhai imperial famille rose and gilded porcelain combines the characteristics of thin glaze, overglaze famille rose, and gilding decoration, requiring high standards for the firing stability, surface smoothness, and adaptability of the base glaze layer. Existing antique-style thin glaze porcelain typically uses feldspar, quartz, kaolin, calcite, and talc as main raw materials, improving glaze density by adjusting flux components, glaze slurry fineness, and firing regime. Rare earth oxides are also used in ceramic glazes to adjust the glass phase structure, melt viscosity, and firing performance. As imperial famille rose and gilded porcelain develops towards stable and mass production, simply optimizing the base glaze ratio or directly adding rare earth components to the entire glaze system, while improving glaze performance to some extent, lacks effective control over the distribution of each component in the glaze slurry and the liquid phase formation position during firing, making it difficult to simultaneously meet the requirements of thin glaze firing, famille rose support, and gilding adhesion.

[0003] Especially under thinner glaze conditions, glaze particles need to undergo continuous changes such as degassing, softening, leveling, and densification during firing. If the low-softening components are disorderly dispersed in the system and form a continuous liquid phase too early, it can easily hinder the expulsion of internal gases, causing pinholes, microbubbles, or localized glaze runs. If the overall softening is insufficient, it will cause increased microscopic undulations on the glaze surface, which is not conducive to the maintenance of subsequent famille rose lines and the stable bonding of the gilding layer. At the same time, if rare earth components exist in a free or uniformly incorporated manner, their regulatory effect on local glass networks and melting behavior is difficult to limit to locations that need to be preferentially sealed and form liquid phase connections. Therefore, existing technologies still need to solve the technical problem of how to synergistically control the particle size, softening behavior, and spatial distribution of different functional glaze particles without relying on increasing the amount of glaze applied, so that the low-softening functional phase has a controlled effect around the skeleton particles and maintains this distribution state during subsequent slurry preparation, thereby taking into account the technical problems of dense glaze formation in thin glazes, stable firing windows, and compatibility with famille rose and gilding interfaces. Summary of the Invention

[0004] To address the aforementioned problems, this invention proposes a rare-earth lanthanum-modified thin glaze material suitable for Dayazhai Imperial Famille Rose Porcelain with Gilded Decoration and its preparation method. By separately constructing a framework-type frit and a lanthanum-modified sealing frit, and utilizing particle size difference, softening temperature difference, and surface anchoring methods, the fine-grained, low-softening lanthanum-modified sealing frit is controlled to distribute on the surface of the framework-type frit particles. Furthermore, after anchoring, they are no longer ball-milled together to maintain the spatial structure of the composite particles. This improves the venting, sealing, and densification behavior during the thin glaze firing process, while simultaneously ensuring the clarity of the famille rose decoration, the stability of the gilding bonding, and the warm, smooth texture of the glaze surface.

[0005] This invention can be achieved through the following technical solutions: A method for preparing a rare-earth lanthanum-modified thin glaze suitable for Dayazhai imperial famille rose porcelain with gold decoration includes the following steps: S1. Mix the framework-type frit raw materials containing potassium feldspar, quartz, kaolin, calcite and talc, and then melt, quench and grind them to obtain the framework-type frit; the D50 of the framework-type frit is 6 to 12 μm and the softening temperature is 1040 to 1100℃. S2. Lanthanum nitrate is compounded with silica sol and aluminum sol to obtain a lanthanum-silicon-aluminum composite precursor, which is then mixed with a sealing frit material containing silicon, boron, zinc, strontium, aluminum and alkali metal sources. After melting, water quenching and grinding, a lanthanum-modified sealing frit is obtained. The lanthanum-modified sealing frit has a D50 of 0.8 to 2.5 μm and a softening temperature of 900 to 960 °C. S3. Disperse the framework-type frit in water, add polyethyleneimine at 0.05-0.20% of the mass of the framework-type frit, adjust the pH of the system to 7.5-9.0, then add the aqueous dispersion of lanthanum-modified pore-sealing frit, and mix at 150-300 r / min for 20-40 min to allow the lanthanum-modified pore-sealing frit to be adsorbed and distributed on the particle surface of the framework-type frit, forming a surface-anchored composite frit unit; S4. The surface-anchored composite frit unit is stirred and slurry-prepared, and after the surface-anchored composite frit unit is formed, the skeleton-type frit and the lanthanum-modified sealing frit are no longer ball-milled together to obtain a rare earth lanthanum-modified thin glaze; wherein, the mass ratio of the skeleton-type frit to the lanthanum-modified sealing frit is (78-82):(18-22); the lanthanum component in the rare earth lanthanum-modified thin glaze is introduced only through the lanthanum-modified sealing frit, and the La2O3 content is 0.8-1.1% based on the total inorganic solid mass of the rare earth lanthanum-modified thin glaze.

[0006] Preferably, in S1, by mass, the skeletal frit raw material includes 45-55 parts of potassium feldspar, 18-25 parts of quartz, 10-15 parts of kaolin, 8-12 parts of calcite, and 4-8 parts of talc.

[0007] Preferably, in S2, the preparation method of the lanthanum-silicon-aluminum composite precursor is as follows: Lanthanum nitrate is added to silica sol and mixed, then aluminum sol and citric acid are added, the pH value of the system is adjusted to 4.0-5.5, and after stirring and drying, it is heat-treated at 550-650℃ to obtain the lanthanum-silicon-aluminum composite precursor; in the lanthanum-silicon-aluminum composite precursor, the mass ratio of SiO2, Al2O3 and La2O3 is (3-6):(1-1.5):1.

[0008] Preferably, the lanthanum-modified sealing frit comprises, by mass percentage of oxides, 44-50% SiO2, 14-17% B2O3, 11-15% ZnO, 6-9% SrO, 5-8% Al2O3, 6-9% total K2O and Na2O, and 4.5-5.0% La2O3, with the sum of the mass percentages of each component being 100%.

[0009] Preferably, in step S4, the slurry is stirred and prepared at 100–300 r / min for 10–30 min, water is added to adjust the specific gravity of the resulting glaze slurry to 1.38–1.42 g / cm3, and then filtered through a 325-mesh sieve to obtain the rare earth lanthanum modified thin glaze.

[0010] The rare earth lanthanum modified thin glaze material prepared by this invention, which is suitable for the Dayazhai Palace Famille Rose Gold-painted Porcelain, includes a skeleton-type frit and a lanthanum modified sealing frit.

[0011] The beneficial effects of this invention are: This invention constructs a thin glaze system with a controlled glazing process by synergistically controlling the particle size, softening behavior, and spatial distribution of a framework-type frit and a lanthanum-modified sealing frit. After surface conditioning, the fine-grained, low-softening-temperature lanthanum-modified sealing frit is adsorbed and distributed on the surface of the coarse-grained, high-softening-temperature framework-type frit. This allows it to preferentially form a local liquid phase around the framework particles during firing, promoting micropore filling while preserving venting channels. Subsequently, the framework-type frit further softens and completes overall vitrification, thereby coordinating the venting, sealing, and densification processes, reducing the risks of pinholes, bubble breakage, and localized glaze flow, and broadening the stable firing window. Simultaneously, the lanthanum component is introduced only through the lanthanum-modified sealing frit, allowing it to concentrate its effect on the local liquid phase formation region along with the fine-grained functional phase. The absence of joint ball milling after surface anchoring helps maintain the coarse-fine grain spatial structure. This can improve the continuity and smoothness of the thin glaze surface, reduce the diffusion of famille rose decorations and improve the bonding stability of the gilding layer, and achieve a synergistic improvement in the firing of the thin glaze, the clarity of the famille rose decorations and the adhesion performance of the gilding, avoiding the simple superposition effect of each component and process measure. Attached Figure Description

[0012] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 The average diffusion width on one side of the pastel pattern and the adhesion retention rate of the gold-painted layer for rare earth lanthanum modified thin glaze. Detailed Implementation

[0013] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.

[0014] Example 1: A method for preparing a rare earth lanthanum-modified thin glaze suitable for Dayazhai imperial famille rose porcelain with gold decoration, comprising the following steps: S1. Weigh out 45 parts potassium feldspar, 18 parts quartz, 10 parts kaolin, 8 parts calcite and 4 parts talc by mass, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a framework-type frit. The D50 of the obtained framework-type frit is 6 μm and the softening temperature is 1040℃. S2. Lanthanum nitrate was added to silica sol and mixed, followed by aluminum sol and citric acid. The pH of the system was adjusted to 4.0. After stirring, the mixture was dried at 100℃ for 12 h, and then heat-treated at 550℃ to obtain a lanthanum-silicon-aluminum composite precursor. The mass ratio of SiO2, Al2O3, and La2O3 in the lanthanum-silicon-aluminum composite precursor was 3:1:1. The amounts of the lanthanum-silicon-aluminum composite precursor and other sealing frit raw materials were calculated based on the final oxide composition, so that the obtained lanthanum-modified sealing frit contained 44% SiO2, 17% B2O3, 15% ZnO, 6% SrO, 5% Al2O3, 8.5% K2O and Na2O, and 4.5% La2O3, with the sum of the mass percentages of each component being 100%. The raw materials were mixed and melted at 1250℃ for 60 min, followed by water quenching, drying, and grinding to obtain a D50 of 0.8. Lanthanum-modified sealing frit with a thickness of μm and a softening temperature of 900℃; S3. Disperse 820 g of framework-type frit in deionized water, add 0.41 g of polyethyleneimine (based on effective ingredient) to make the amount of polyethyleneimine added 0.05% of the mass of the framework-type frit, and adjust the pH of the system to 7.5. Separately, disperse 180 g of lanthanum-modified pore-sealing frit in deionized water, add the resulting dispersion to the framework-type frit dispersion system, and mix at 150 r / min for 20 min to allow the lanthanum-modified pore-sealing frit to be adsorbed and distributed on the surface of the framework-type frit particles, forming surface-anchored composite frit units. The mass ratio of framework-type frit to lanthanum-modified pore-sealing frit is 82:18. Based on the total mass of inorganic solids, the La2O3 content in the resulting system is 0.81%. S4. After forming the surface-anchored composite frit unit, no further ball milling is performed. The slurry is stirred and adjusted at 100 r / min for 10 min. Water is added to adjust the specific gravity of the glaze slurry to 1.38 g / cm3. After filtration through a 325-mesh sieve, rare earth lanthanum modified thin glaze is obtained.

[0015] Example 2: A method for preparing a rare earth lanthanum-modified thin glaze suitable for Dayazhai imperial famille rose porcelain with gold decoration, comprising the following steps: S1. Weigh out 50 parts potassium feldspar, 21.5 parts quartz, 12.5 parts kaolin, 10 parts calcite and 6 parts talc by weight, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a framework-type frit. The D50 of the obtained framework-type frit is 9 μm and the softening temperature is 1070℃. S2. Lanthanum nitrate was added to silica sol and mixed, followed by aluminum sol and citric acid. The pH of the system was adjusted to 4.75. After stirring, the mixture was dried at 100℃ for 12 h, and then heat-treated at 600℃ to obtain a lanthanum-silicon-aluminum composite precursor. The mass ratio of SiO2, Al2O3, and La2O3 in the lanthanum-silicon-aluminum composite precursor was 4.5:1.25:1. The amounts of the lanthanum-silicon-aluminum composite precursor and other sealing frit raw materials were calculated based on the final oxide composition, so that the obtained lanthanum-modified sealing frit contained 50% SiO2, 14% B2O3, 11% ZnO, 7.75% SrO, 6.5% Al2O3, 6% K2O and Na2O, and 4.75% La2O3, with the sum of the mass percentages of each component being 100%. The raw materials were mixed and melted at 1250℃ for 60 min, followed by water quenching, drying, and grinding to obtain a D50 of 1.65. Lanthanum-modified sealing frit with a thickness of μm and a softening temperature of 930℃; S3. Disperse 800 g of framework-type frit in deionized water, add 1.00 g of polyethyleneimine (based on effective ingredient) to make the amount of polyethyleneimine added 0.125% of the mass of the framework-type frit, and adjust the pH of the system to 8.25. Separately, disperse 200 g of lanthanum-modified sealing frit in deionized water, add the resulting dispersion to the framework-type frit dispersion system, and mix at 225 r / min for 30 min to obtain a surface-anchored composite frit unit. The mass ratio of framework-type frit to lanthanum-modified sealing frit is 80:20. The La2O3 content in the obtained system is 0.95% based on the total mass of inorganic solids. S4. After forming the surface-anchored composite frit unit, no further ball milling is performed. The slurry is stirred and adjusted at 200 r / min for 20 min. Water is added to adjust the specific gravity of the glaze slurry to 1.40 g / cm3. After filtration through a 325-mesh sieve, rare earth lanthanum modified thin glaze is obtained.

[0016] Example 3: A method for preparing a rare earth lanthanum-modified thin glaze suitable for Dayazhai imperial famille rose porcelain with gold decoration, comprising the following steps: S1. Weigh out 55 parts potassium feldspar, 25 parts quartz, 15 parts kaolin, 12 parts calcite and 8 parts talc by weight, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a framework-type frit. The D50 of the obtained framework-type frit is 12 μm and the softening temperature is 1100℃. S2. Lanthanum nitrate was added to silica sol and mixed, followed by aluminum sol and citric acid. The pH of the system was adjusted to 5.5. After stirring, the mixture was dried at 100℃ for 12 h, and then heat-treated at 650℃ to obtain a lanthanum-silicon-aluminum composite precursor. The mass ratio of SiO2, Al2O3, and La2O3 in the lanthanum-silicon-aluminum composite precursor was 6:1.5:1. The amounts of the lanthanum-silicon-aluminum composite precursor and other sealing frit raw materials were calculated based on the final oxide composition, so that the obtained lanthanum-modified sealing frit contained 44% SiO2, 14% B2O3, 11% ZnO, 9% SrO, 8% Al2O3, 9% K2O and Na2O, and 5.0% La2O3, with the sum of the mass percentages of each component being 100%. The raw materials were mixed and melted at 1250℃ for 60 min, followed by water quenching, drying, and grinding to obtain a D50 of 2.5. Lanthanum-modified sealing frit with a thickness of μm and a softening temperature of 960℃; S3. Disperse 780 g of framework-type frit in deionized water, add 1.56 g of polyethyleneimine (based on effective ingredient) to make the amount of polyethyleneimine added 0.20% of the mass of the framework-type frit, and adjust the pH of the system to 9.0; separately disperse 220 g of lanthanum-modified sealing frit in deionized water, add the resulting dispersion to the framework-type frit dispersion system, and mix at 300 r / min for 40 min to obtain a surface-anchored composite frit unit; the mass ratio of framework-type frit to lanthanum-modified sealing frit is 78:22; the La2O3 content in the obtained system is 1.10% based on the total mass of inorganic solids; S4. After forming the surface-anchored composite frit unit, no further ball milling is performed. The slurry is stirred and adjusted at 300 r / min for 30 min. Water is added to adjust the specific gravity of the glaze slurry to 1.42 g / cm3. After filtration through a 325-mesh sieve, rare earth lanthanum modified thin glaze is obtained.

[0017] Comparative Example 1: The difference between this comparative example and Example 1 is that the skeleton-type frit and the lanthanum-modified sealing frit are not subjected to polyethyleneimine surface conditioning and surface anchoring treatment, but are directly mixed and pulped in the same mass ratio.

[0018] The preparation method of the rare earth lanthanum modified thin glaze in this comparative example includes the following steps: S1. Weigh out 45 parts potassium feldspar, 18 parts quartz, 10 parts kaolin, 8 parts calcite and 4 parts talc by mass, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a framework-type frit. The D50 of the obtained framework-type frit is 6 μm and the softening temperature is 1040℃. S2. Lanthanum nitrate was added to silica sol and mixed, followed by aluminum sol and citric acid. The pH of the system was adjusted to 4.0. After stirring, the mixture was dried at 100℃ for 12 h and then heat-treated at 550℃ to obtain a lanthanum-silicon-aluminum composite precursor, wherein the mass ratio of SiO2, Al2O3 and La2O3 was 3:1:1. The raw materials were prepared according to the final oxide composition so that the obtained lanthanum-modified sealing frit contained 44% SiO2, 17% B2O3, 15% ZnO, 6% SrO, 5% Al2O3, 8.5% K2O and Na2O, and 4.5% La2O3. The raw materials were mixed and melted at 1250℃ for 60 min. After water quenching, drying and grinding, a lanthanum-modified sealing frit with a D50 of 0.8 μm and a softening temperature of 900℃ was obtained. S3. Take 820 g of skeleton-type frit and 180 g of lanthanum-modified sealing frit, add deionized water to form a dispersion, without adding polyethyleneimine, adjust the pH of the system to 7.5 and mix directly, stir at 150 r / min for 20 min, so that the two frits are dispersed in the system in a free mixing state. S4. Continue stirring and adjusting the slurry at 100 r / min for 10 min, add water to adjust the specific gravity of the slurry to 1.38 g / cm3, filter through a 325 mesh sieve to obtain rare earth lanthanum modified thin glaze; the La2O3 in the obtained thin glaze accounts for 0.81% of the total mass of inorganic solids.

[0019] Comparative Example 2: The difference between this comparative example and Example 1 is that after the skeleton-type frit and the lanthanum-modified sealing frit form a surface-anchored composite frit unit, they are then ball-milled together, which disrupts the surface-anchored distribution state.

[0020] The preparation method of the rare earth lanthanum modified thin glaze in this comparative example includes the following steps: S1. Weigh out 45 parts potassium feldspar, 18 parts quartz, 10 parts kaolin, 8 parts calcite and 4 parts talc by mass, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a skeleton-type frit with D50 of 6 μm and softening temperature of 1040℃. S2. Lanthanum nitrate was added to silica sol and mixed, followed by aluminum sol and citric acid. The pH of the system was adjusted to 4.0. After stirring, the mixture was dried at 100℃ for 12 h and then heat-treated at 550℃ to obtain a lanthanum-silicon-aluminum composite precursor, wherein the mass ratio of SiO2, Al2O3 and La2O3 was 3:1:1. The raw materials were prepared according to the final oxide composition so that the lanthanum-modified sealing frit contained 44% SiO2, 17% B2O3, 15% ZnO, 6% SrO, 5% Al2O3, 8.5% K2O and Na2O, and 4.5% La2O3. The raw materials were melted at 1250℃ for 60 min, and then quenched, dried and ground to obtain a lanthanum-modified sealing frit with a D50 of 0.8 μm and a softening temperature of 900℃. S3. Disperse 820 g of skeleton-type frit in deionized water, add 0.41 g of polyethyleneimine (based on effective ingredients) to make the amount added 0.05% of the mass of the skeleton-type frit, and adjust the pH of the system to 0.5; separately disperse 180 g of lanthanum-modified sealing frit in deionized water, add the resulting dispersion to the skeleton-type frit dispersion system, and mix at 150 r / min for 20 min to form a surface-anchored composite frit unit; S4. Transfer the surface-anchored composite frit slurry into a ball mill and ball mill it together at 200 r / min for 20 min. After ball milling, stir and adjust the slurry at 100 r / min for 10 min, add water to adjust the specific gravity of the glaze slurry to 1.38 g / cm3, filter it through a 325 mesh sieve to obtain rare earth lanthanum modified thin glaze. In the obtained thin glaze, La2O3 accounts for 0.81% of the total mass of inorganic solids.

[0021] Comparative Example 3: The difference between this comparative example and Example 1 is that the lanthanum component is not limited to the lanthanum-modified sealing frit, but an equal amount of La2O3 is directly added to the thin glaze system composed of the framework frit and the sealing frit, while keeping the total La2O3 content in the thin glaze consistent with that in Example 1.

[0022] The preparation method of the rare earth lanthanum modified thin glaze in this comparative example includes the following steps: S1. Weigh out 45 parts potassium feldspar, 18 parts quartz, 10 parts kaolin, 8 parts calcite and 4 parts talc by mass, mix them evenly and melt them at 1350℃ for 60 min. Quench the melt with water, dry it and grind it to obtain a skeleton-type frit with D50 of 6 μm and softening temperature of 1040℃. S2. The non-lanthanum oxide composition of the 180 g lanthanum-modified sealing frit after deducting 8.10 g La2O3 was prepared according to the method in Example 1, so that the resulting sealing frit contained 79.2 g SiO2, 30.6 g B2O3, 27 g ZnO, 10.8 g SrO, 9 g Al2O3, and a total of 15.3 g K2O and Na2O, corresponding to a total mass of 171.9 g. Based on the mass of the sealing frit itself, its oxide composition was converted to 46.07% SiO2, 17.80% B2O3, 15.71% ZnO, 6.28% SrO, 5.24% Al2O3, and a total of 8.90% K2O and Na2O. The corresponding raw materials were mixed and melted at 1250℃ for 60 min, then water-quenched, dried, and ground to obtain a D50 of 0.8 μm for the resulting sealing frit. S3. Take 820 g of skeleton-type frit and disperse it in deionized water. Add 0.41 g of polyethyleneimine (based on the effective ingredient) and adjust the pH of the system to 7.5. Separately, disperse 171.9 g of sealing frit in deionized water. Add the resulting dispersion to the skeleton-type frit dispersion system and mix at 150 r / min for 20 min. S4. Add 8.1 g of La2O3 powder to the slurry obtained in S3 and stir at 100 r / min for 10 min to directly disperse lanthanum oxide in the thin glaze system. The resulting system is not ball-milled again. Then, water is added to adjust the specific gravity of the glaze slurry to 1.38 g / cm3. After filtration through a 325 mesh sieve, a rare earth lanthanum modified thin glaze is obtained. The total mass of the skeleton frit, the sealing frit, and the added La2O3 is 1 kg, of which 8.1 g is La2O3. Therefore, La2O3 accounts for 0.81% of the total mass of inorganic solids in the obtained thin glaze.

[0023] Performance testing 1. Defect density test on thin glaze surface After high-temperature firing, the samples were placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours. A 20 mm × 20 mm test area was marked at the center of the glaze surface and at one of the four four-zone locations on each sample, with a total of 5 non-overlapping test areas set for each sample.

[0024] Each test area was observed using a stereomicroscope at 20x magnification. Pinholes, broken bubbles, and surface bubbles with obvious openings with a diameter of not less than 0.1 mm were counted on the glaze surface. For irregularly shaped defects, their maximum outer dimension was used as the defect size; interconnected defects with independent openings were counted separately.

[0025] Calculate the surface defect density using the following formula: D=N / A In the formula: D represents the surface defect density of the thin glaze; N is the total number of defects obtained from the statistics in the 5 test areas; A represents the total area of ​​the test area; in this test, A = 20 cm².

[0026] At the same time, observe whether there are visible glaze shrinkage, local glaze flow, and bubble aggregation phenomena on the edge of the sample and the glaze surface.

[0027] 2. Pastel pattern diffusion width test Take a sample that has been fired at high temperature with the base glaze, and use the same batch of famille rose pigments to create five parallel straight lines on the glaze surface. Each line is 30 mm long and the initial width is controlled to be 1.00 ± 0.03 mm. The amount of famille rose pigments used, the preparation method, the thickness of the paint application, and the firing process are kept completely consistent for each group.

[0028] Before firing, the actual width of each stripe was measured at 10 equally spaced positions using a digital microscope to obtain the average width W0 before firing. After firing and cooling to room temperature, the width of the stripe was measured again at the same positions to obtain the average width W1 after firing.

[0029] The average diffusion width of the pattern on one side is calculated using the following formula: We = (W1 - W0) / 2 In the formula: We represents the average diffusion width of the pastel pattern on one side; W0 represents the average width of the decoration before firing; W1 represents the average width of the decoration after firing.

[0030] A total of 250 locations were measured for each group of samples, and the average value was taken. When irregular diffusion occurred at the edge of the local pattern, the distance between the original pattern boundary and the outermost continuous colored boundary after diffusion was taken as the diffusion width.

[0031] 3. Gold plating layer adhesion retention rate test Another sample with the base glaze fired at high temperature was taken, and three rectangular gold-painted areas of 20 mm × 30 mm were set on the surface of each sample. The same batch of gold solution was used and applied evenly to the test area with the same amount. The same gold-painting firing process was used for firing, and then the samples were cooled to room temperature and left to stand for 24 hours.

[0032] An image acquisition device was used to record the gold-plated area before the tape was peeled off, and the area A0 of the initial intact gold layer was determined by image analysis.

[0033] Acrylic pressure-sensitive tape of the same batch and 25 mm width was used to cover the gold-painted area. A 2 kg rubber roller was used to roll the tape back and forth three times along its length. After standing for 60 seconds, the sample was fixed and the tape was peeled off continuously at a speed of 300 mm / min in a 180° direction. Only one peel test was performed on each gold-painted area.

[0034] After the tape was peeled off, the image of the gold-painted area was re-acquired under the same lighting, shooting distance and magnification as before peeling, and the area A1 of the gold layer that was still continuously attached to the glaze was determined by image analysis method.

[0035] The adhesion retention rate of the gold plating layer is calculated using the following formula: R = A1 / A0 × 100 In the formula: R represents the adhesion retention rate of the gold plating layer; A0 represents the area of ​​the complete gold-plated layer before the tape is peeled off; A1 represents the area of ​​the gold-painted layer that remains intact on the glaze after the tape is peeled off.

[0036] At the same time, observe whether the gold layer shows flaking, edge lifting, or local cracking.

[0037] 4. Stable firing temperature window test Samples were prepared using the same porcelain blanks and glazing methods as those used in the tests described above, with the target glaze thickness after high-temperature firing controlled to be 0.18–0.24 mm. Seven maximum firing temperatures were set for each group of thin glazes: 1210℃, 1220℃, 1230℃, 1240℃, 1250℃, 1260℃, and 1270℃. Each group of samples was heated from room temperature to 1190℃ at a rate of 3℃ / min, and then further heated at a rate of 1.5℃ / min to the corresponding maximum firing temperature. The samples were held at the maximum firing temperature for 30 min, and then slowly cooled to room temperature using the same procedure. Three parallel samples were set up at each temperature point. After firing, the samples were placed at room temperature for 24 hours, and the glaze surface was observed according to the above-described thin glaze surface defect test method. The temperature point that simultaneously meets the following conditions is determined to be the qualified firing temperature: (1) The glaze layer is continuous and intact, with no obvious glaze shrinkage or exposed body; (2) No obvious glaze flow or local glaze accumulation visible to the naked eye; (3) No obvious large-area pinholes, broken bubbles, or bubble aggregation; (4) The glaze surface has no obvious opacity, over-firing, local crystallization or abnormal opacity; (5) All three parallel samples at the same temperature point meet the above requirements.

[0038] The difference between the lowest and highest firing temperatures Tmin and the highest firing temperature Tmax within a continuous qualified temperature range is defined as the stable firing temperature window. ΔT = Tmax - Tmin In the formula: ΔT is the stable firing temperature window; Tmax is the highest firing temperature within the continuous qualified temperature range; Tmin is the lowest firing temperature within the continuous acceptable temperature range.

[0039] Table 1. Test results of various properties of rare earth lanthanum modified thin glaze.

[0040] As can be seen from the results in the table, Examples 1-3 all exhibited low surface defect density of thin glaze, small diffusion width of famille rose decoration, high adhesion retention rate of gilding layer, and wide stable firing temperature window. The surface defect density was only 0.12-0.20 defects / cm2, the average diffusion width of famille rose decoration on one side was 41-46 μm, the adhesion retention rate of gilding layer reached 96.5-97.8%, and the stable firing temperature window reached 50-60℃. The above results indicate that the present invention does not rely solely on lanthanum oxide or frits with different softening temperatures to function. Instead, it controls the position of the low-softening functional phase by pre-anchoring the fine-grained, low-softening lanthanum-modified sealing frit on the surface of the coarse-grained skeletal frit. Furthermore, by avoiding joint ball milling after anchoring, the spatial structure of the particles is maintained, allowing for more coordinated local softening, venting, sealing, and subsequent overall densification during firing. Simultaneously, the lanthanum component is confined within the sealing frit, which facilitates the formation of a more stable local glass network, ultimately achieving a balance between thin glaze firing stability, preservation of famille rose decoration boundaries, and bonding performance at the gilding interface.

[0041] Compared to Example 1, Comparative Example 1 eliminated the polyethyleneimine surface conditioning and surface anchoring of the two types of frits, and only used direct mixing. The surface defect density of the thin glaze increased from 0.18 defects / cm² to 0.92 defects / cm², and the stable firing temperature window narrowed from 50°C to 20°C. Simultaneously, the diffusion width of the pastel pattern increased, and the adhesion retention rate of the gilding layer decreased. This indicates that simply having two types of frits with different particle sizes and softening temperatures is insufficient to achieve the comprehensive effect of this invention. The key lies in the controlled spatial distribution of the low-softening fine-grained frits around the skeletal particles. Although Comparative Example 2 first formed surface-anchored composite frit units, subsequent co-ball milling increased its surface defect density to 0.61 defects / cm² and decreased the stable firing temperature window to 30°C. This indicates that maintaining the particle structure after forming the anchoring structure is also a necessary condition. Subsequent co-ball milling weakens the original spatial relationship between the two types of frits, thereby reducing the staged softening and sealing effect. In Comparative Example 3, with the same total La2O3 content as in Example 1, the lanthanum component was directly added to the thin glaze system, and the diffusion width of the pastel pattern increased to 84 μm, while the adhesion retention rate of the gold-painted layer decreased to 86.7%.

[0042] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a rare-earth lanthanum-modified thin glaze suitable for Dayazhai imperial famille rose porcelain with gold decoration, characterized in that, Includes the following steps: S1. Mix the framework-type frit raw materials containing potassium feldspar, quartz, kaolin, calcite and talc, and then melt, quench and grind them to obtain the framework-type frit; the D50 of the framework-type frit is 6 to 12 μm and the softening temperature is 1040 to 1100℃. S2. Lanthanum nitrate is compounded with silica sol and aluminum sol to obtain a lanthanum-silicon-aluminum composite precursor, which is then mixed with a sealing frit material containing silicon, boron, zinc, strontium, aluminum and alkali metal sources. After melting, water quenching and grinding, a lanthanum-modified sealing frit is obtained. The lanthanum-modified sealing frit has a D50 of 0.8 to 2.5 μm and a softening temperature of 900 to 960 °C. S3. Disperse the framework-type frit in water, add polyethyleneimine at 0.05-0.20% of the mass of the framework-type frit, adjust the pH of the system to 7.5-9.0, then add the aqueous dispersion of lanthanum-modified pore-sealing frit, and mix at 150-300 r / min for 20-40 min to allow the lanthanum-modified pore-sealing frit to be adsorbed and distributed on the particle surface of the framework-type frit, forming a surface-anchored composite frit unit; S4. The surface-anchored composite frit unit is stirred and slurry-prepared, and after the surface-anchored composite frit unit is formed, the skeleton-type frit and the lanthanum-modified sealing frit are no longer ball-milled together to obtain a rare earth lanthanum-modified thin glaze; wherein, the mass ratio of the skeleton-type frit to the lanthanum-modified sealing frit is (78-82):(18-22); the lanthanum component in the rare earth lanthanum-modified thin glaze is introduced only through the lanthanum-modified sealing frit, and the La2O3 content is 0.8-1.1% based on the total inorganic solid mass of the rare earth lanthanum-modified thin glaze.

2. The method for preparing rare earth lanthanum-modified thin glaze material suitable for Dayazhai court famille rose enamel porcelain according to claim 1, characterized in that, In S1, by mass, the framework-type frit raw material includes 45-55 parts of potassium feldspar, 18-25 parts of quartz, 10-15 parts of kaolin, 8-12 parts of calcite and 4-8 parts of talc.

3. The method for preparing rare earth lanthanum-modified thin glaze material suitable for Dayazhai court famille rose enamel porcelain according to claim 1, characterized in that, The preparation method of the lanthanum-silicon-aluminum composite precursor in S2 is as follows: Lanthanum nitrate is added to silica sol and mixed, then aluminum sol and citric acid are added, the pH value of the system is adjusted to 4.0-5.5, and after stirring and drying, it is heat-treated at 550-650℃ to obtain the lanthanum-silicon-aluminum composite precursor; in the lanthanum-silicon-aluminum composite precursor, the mass ratio of SiO2, Al2O3 and La2O3 is (3-6):(1-1.5):

1.

4. The preparation method of rare earth lanthanum modified thin glaze material adapted to Dayazhai Palace Famille Rose Gold-Painted Porcelain according to claim 1, characterized in that, The lanthanum-modified sealing frit, by mass percentage of oxides, comprises 44-50% SiO2, 14-17% B2O3, 11-15% ZnO, 6-9% SrO, 5-8% Al2O3, 6-9% total K2O and Na2O, and 4.5-5.0% La2O3, with the sum of the mass percentages of each component being 100%.

5. The method for preparing rare earth lanthanum-modified thin glaze material suitable for Dayazhai court famille rose enamel porcelain according to claim 1, characterized in that, In step S4, the slurry is stirred and prepared at 100–300 r / min for 10–30 min, water is added to adjust the specific gravity of the resulting glaze slurry to 1.38–1.42 g / cm3, and then filtered through a 325-mesh sieve to obtain the rare earth lanthanum modified thin glaze.

6. A rare-earth lanthanum-modified thin glaze material suitable for Dayazhai Palace Famille Rose Gold-Painted Porcelain, characterized in that, The rare earth lanthanum modified thin glaze is prepared by any one of claims 1 to 5, including a skeleton-type frit and a lanthanum modified sealing frit.